Participation or What? Local Experiences and Perceptions of Household Performance Contracting in Rwanda. Issue 2 (3rd May 2016) - Hasselskog, Malin
Abstract : This article analyses the participation entailed in the Rwandan practice of household performance contracting, and discusses likely effects. Participation constitutes an intrinsic part of development practice and theory. Approaches and aims, however, differ, for example, between community members making decisions and being informed, and between empowerment and efficiency. The Rwandan government, eloquently ascribing to the participation discourse, has launched a number of programmes alluding to traditional participatory practices. One of these is performance contracting, imihigo, presented as involving the population in formulation, implementation and monitoring of national policy. As part of the programme, every head of household signs a contract, committing to, within a specific timeframe, reach a number of detailed targets. In order to investigate local experiences and perceptions of household imihigo, officials and residents in two communities have been interviewed. Responses are analysed in light of participation theories, with regard to in what and how residents participate, and what the likely effects are. Findings show that household imihigo targets derive from the state, that poor people are made to concentrate their efforts to reaching these targets, also at the expense of more immediate needs, that residents are closely monitored on partly highly personal issues, and that individual households' performance is publically announced. The system is found to entail participation in the implementation of national policy, but not in formulation or monitoring. It is argued that, while household imihigo increases efficiency and possibly government legitimacy, it does not provide for local relevance or empowerment, but rather constitutes a governing tool.